SEJARAH PRA KEMUNCULAN NOVEL ARAB - Moh. Wakhid Hidayat (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
Novel (riwayah) is categorized as a genre of modern Arabic literature. The birth of this genre has something to do with the revival period of Arabic in general. Yet the pre-natal of this new genre in Arab world is left undiscussed. This research aims at disclosing the birth of Arabic novel. It is found that Egypt has been the center of the labor of this genre. Its pre-natal period is marked by the translation of the Western literature and the resurrection of the genre of maqamah. There are some arguments on the situation and condition of the pre-natal of the Arabic novel. First, it was imported from the west. The second argument is that novel is indigenous genre, and the third is that novel is rooted from both classical Arabic and modern Western world.